Innovative Use of Magnetic Crowns for Pulp Vitality and Regeneration - Amir Abbas Sayed* (Archives of Community Medicine and Public Health, 2025)
Abstract Preserving the vitality of the dental pulp is critical in maintaining tooth longevity, yet conventional restorations often lead to pulp shrinkage or necrosis, ultimately requiring endodontic therapy. We propose a novel dental crown design incorporating magnetic elements to achieve two core objectives: (1) maintain pulp vitality by stimulating local circulation and cell viability, and (2) promote controlled ossification within the pulp chamber using repelling magnetic fields, potentially obviating the need for root canal treatment. This concept leverages existing literature on magnetic biomodulation, pulpal regeneration, and mineralization to introduce a non-invasive therapeutic pathway. We present the scientific rationale, conceptual design, and a proposed mechanism of action. The concept is expected to initiate further laboratory research and clinical feasibility testing in collaboration with academic or biomaterial development laboratories.